2018
DOI: 10.15570/actaapa.2018.31
|View full text |Cite
|
Sign up to set email alerts
|

Multiorgan involvement of Behçet’s disease in a young woman

Abstract: Behçet's disease is a rare disorder of unknown etiology that is classified as a systemic vasculitis. The prevalence of the disease is high in countries in the Far East, Mediterranean Basin, and East Asia. Thus, it is also known as the Silk Road Disease. Behçet's disease is characterized by recurrent oral aphthous ulcers, genital sores, and ocular lesions. However, it can present with severe clinical manifestations as a result of cardiovascular system, central nervous system, and gastrointestinal tract involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Our study also demonstrated that treatment with mepolizumab was associated with a significant reduction in eosinophil counts, which correlated with improved asthma control, as evidenced by higher ACT scores. These findings are consistent with previous studies demonstrating the efficacy of mepolizumab in reducing exacerbation rates and improving asthma control in patients with SEA (5,6,15,29). However, in our research, mepolizumab-treated patients did not exhibit a marked shift in serum total IgE levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study also demonstrated that treatment with mepolizumab was associated with a significant reduction in eosinophil counts, which correlated with improved asthma control, as evidenced by higher ACT scores. These findings are consistent with previous studies demonstrating the efficacy of mepolizumab in reducing exacerbation rates and improving asthma control in patients with SEA (5,6,15,29). However, in our research, mepolizumab-treated patients did not exhibit a marked shift in serum total IgE levels.…”
Section: Discussionsupporting
confidence: 93%
“…A study evaluating response rates, baseline IgE levels, and total IgE levels after omalizumab treatment in patients with CSU found that alterations in IgE levels can predict the outcome of omalizumab treatment (5). In another study, Tamer et al demonstrated that omalizumab reduced serum total eosinophil levels in a significant proportion of CSU patients, indicating that serum eosinophil count might be a valuable marker for guiding treatment decisions (6).…”
Section: Biologicalmentioning
confidence: 99%